Robin - Itzkoff, Dave (New York : Henry Holt and Company, 2018)
"From his rapid-fire stand-up riffs to his breakout role in Mork & Mindy and his powerful Academy Award-winning performance in Good Will Hunting, Robin Williams was a singularly innovative actor and comedian. He foten came across as a man possessed, hilding forth on culture, politics, and personal revelation -- all with mercurial, tongue-twsiting intensity as he inhabited and shed one character after another. But as Dave Itzkoff shows in this revelatory biography, Williams's brilliance masked a deep well of conflicting emotions and self-doubt. In is comedy and in celebrated films such as Dead Poets; Good Morning, Vietnam; The Fisher King; Aladdin; and Mrs. Doubtfire he showcased his limitless gift for improvisation, bringing his caracters to life and using humor to seek deeper truths. Itzkoff also shows how Williams struggled mightily with addiction and depression and with a debilitating condition at the end of is life that afected him in way his fans never knew. Drawing on more than a hundred original interviews with family, friends, and colleagues, as well as extnesive archival research, Robin is a fesh and original look at a performer whose work touched so many of our lives"--
Includes bibliographical references (pages 449-508) and index.
Keywords: Williams, Robin, -- 1951-2014.; Comedians -- United States -- Biography; Actors -- United States -- Biography; Biographies